Decision 15/9 and the Nagoya Protocol: Who should get what in the Multilateral Benefit-Sharing Mechanism? - Joseph H. Vogel; Natasha C. Jiménez-Revelles; Xavier A. Maldonado-Ramírez de Arellano (South Centre, 2024)
Article 10 of the Nagoya Protocol (NP), "Global Multilateral Benefit-Sharing Mechanism" (GMBSM), asks Parties to consider the distribution of benefits derived from the utilization of genetic resources in transboundary situations. A literature exists which applies the economics of information to genetic resources, when interpreted as "natural information". The policy implication would incentivize reduction in the drivers of mass extinction, through economic rents in royalty obligations. Fifteen cases become thought experiments on how to share royalty income. A sixteenth case addresses the TP53 gene in elephants, which may revolutionize oncology. In parallel to Article 10 of the NP is Decision 15/9 of the fifteenth Conference of the Parties to the Convention on Biological Diversity. That Decision establishes a "multilateral benefit-sharing mechanism from the use of digital sequence information on genetic resources". Redundancy with the GMBSM is only apparent. The Decision omits rents and thus renders its mechanism inefficient, unfair and inequitable.
Keywords: 300; Access and Benefit-Sharing (ABS); Biodiversity; Bounded Openness; Convention on Biological Diversity (CBD); Decision 15/9; Digital Sequence Information (DSI); E.O. Wilson; Genetic Resources; Global Multilateral Benefit-Sharing Mechanism (GMBSM); Half-Earth; Intellectual Property; Mass Extinction; Nagoya Protocol; Natural Information; Royalty; United Nations Framework Convention on Climate Change (UNFCCC